Bran Bar Product Development for Athletes (Organoleptic Assessment and Nutritional Content) - Sholichin; Hizni, Alina; Yuhandini, Diyah Sri (Media Informasi, 2025)
Background: Rice milling produces a by-product of rice bran (8-12%) with good nutritional content, which can be used as raw material for making snack bars to optimize athlete performance. Objectives: The study aimed to analyze the organoleptic assessment and nutritional content of bran bars as snack bars for athletes. Methods: The research was conducted from May to November 2024 at the D III Nutrition Study Programme Cirebon and Saraswanti Indo Global Laboratory. Organoleptic assessment using a completely randomized design and 2 repetitions by 32 students who are active in sports, on the parameters of colour, aroma, taste, texture, and overall with a rating scale of 1 (very dislike), 2 (dislike), 3 (normal), 4 (like), and 5 (very like). Nutritional content analysis included moisture, ash, protein, fat, carbohydrate, fiber, iron, and energy content. The organoleptic assessment was analyzed using the one-way ANOVA test and Duncan's test to determine differences between treatments, while nutrient content was analyzed descriptively. Results: Organoleptic assessment showed significant differences between treatments in colour, aroma, taste, texture, and overall parameters (p-value 0.000 <0.05). The best formula based on organoleptic assessment was treatment P2 (average 3.96), almost the same as the control treatment (F0) (average 3.94). However, based on nutritional content, treatment F8 had the lowest water content (15.27 g), highest ash content (4.03 g), lowest fat content (16.28 g), highest protein content (9.24g), highest iron content (8.07 g) and high dietary fiber content (8.07 g). Conclusion: The best formula based on organoleptic assessment is F2, but based on nutritional content, F8 is the best formula.